(untitled) (Asian Business Research, 2022)
With the rapid expansion of the scale of China’s capital market, the disclosure of accounting information of listed companies is not standardized and the problem of information transparency is becoming more and more prominent. This paper analyzes the present situation and existing problems of the accounting information supervision system of listed companies in China from three aspects: the internal system supervision of listed companies, the supervision of government legal system and the supervision of social intermediary system, and puts forward some countermeasures for perfecting the supervision of accounting information of listed companies in China.